Articular cartilage: Chemical, Physical, and Tribological Properties - Aleksandra Mreła; Zenon Pawlak (Journal of New Developments in Chemistry, 2018)
The cartilage surface was characterized using wettability test fresh and depleted AC samples. In this work, we demonstrated experimentally that the cartilage smart biomaterial at varies pH is sensitive to friction and introduces a novel concept in joint lubrication on charged surfaces.The surface charge density of the articular cartilage surface is related to the amphoteric character of phospholipids, PLs functional groups (-NH3+) and (-PO4-). The maximum surface energy of AC was found to occur at pH for isoelectric point 4.5 (H3N+(CH2)n PO4- -R1R2) and with a wide range minimum of pH 6.5 to 9.5 of the phospholipidic membrane covering biological pH 7.4 lubrication condition. The hydrophilic and hydrophobic character of cartilage was determined.
Keywords: articular cartilage